Expression of HER2 in high-grade urothelial carcinoma based on Chinese expert consensus and the clinical effects of disitamab vedotin-tislelizumab combination therapy in the treatment of advanced patients - Zhu, Kejia; Chang, Yao; Zhao, Delong; Guo, Andong; Cao, Jishuang; Wu, Chenrui; Guan, Yong; Ding, Sentai (Frontiers in Pharmacology, 2024)
Background: A vast number of researchers have discovered high levels of human epidermal growth factor receptor-2 (HER2) expression in urothelial carcinoma (UC), but they do not use a uniform scoring system. Based on the 2021 edition of clinical pathological expert consensus on HER-2 testing in UC in China, we investigated the expression level and clinical significance of HER2 in high-grade UC. Furthermore, we looked at the prognosis of patients with locally advanced/metastatic UC after combining HER2 targeting antibody-drug conjugates (ADC) medication disitamab vedotin (DV) with programmed cell death protein 1 (PD-1) inhibitor tislelizumab.Patients and Methods: From 2019 to 2022, we collected paraffin specimens of UC from the Department of Urology at the Provincial Hospital Affiliated to Shandong First Medical University. HER2 expression-related factors were investigated. Patients with advanced UC who have failed systemic chemotherapy at least once and had received immune checkpoint inhibitor (ICI) medication during second-line treatment were selected and treated with DV in combination with tislelizumab. We assessed the therapy's efficacy and safety.Results: 185 patients with high-grade UC were included in this investigation. 127 patients (68.7%) were HER2 positive (IHC 2+/3+) according to the 2021 Clinical pathological expert consensus on HER2 testing in UC in China. The clinical stage of UC differed statistically significantly between the HER2-and HER2+ groups (P=0.019). Sixteen advanced UC patients were treated with DV and tislelizumab for a median of 14 months. The disease control rate was 87.5%, while the objective response rate (ORR) was 62.5%. The ORR of HER2+ individuals was higher than that of HER2individuals (70.0% vs. 50.0%). The median progression-free survival or overall survival was not reached. In this study, the incidence of treatment-related adverse events was 68.8% (11/16), with all of them being grade 1 or 2 adverse reactions.HER2 protein expressed at a high percentage in UC, and 68.7% patients expressed HER2 positive (IHC 2+/3+). HER2+ expression is positively correlated with higher clinical stage of UC. HER2 targeted ADC drug disitamab vedotin combining with PD-1 inhibitor tislelizumab has shown efficacy, safety and controllable adverse reactions in the treatment of advanced UC.